PRESIDENTIAL SYSTEM OF GOVERNMENT AND POLITICAL STABILITY (Third Sector Social Economic Review, 2018)
With the overpowering of rulership in the Middle Ages, the struggles against aristocracy and absolute monarchy revealed the need to limit the power, i.e. the separation of the legislative, executive and judicial powers.The level at which the powers are to be separated, in other words rigid or soft separation of powers, led to the emergence of different governmental systems. Government systems, which are classified on the basis of rigid or soft separation of the forces, are shaped in the direction of the parliamentary system and the presidential system. Government systems, such as the semi-presidential and presidential government systems, are also implemented as different variations of the parliamentary system and the presidential system.It is possible to say that the system of government is influential on political stability. System of government used should not only ensure the separation of forces but also the political stability of the country at the same time. In a country where political stability cannot be achieved, it will become difficult to achieve economic and social prosperity, social peace and trust. Therefore, changes can be made in the system of government to strengthen political stability and reduce the likelihood of adverse situations occurring.The main purpose of this study is to examine how effective the presidential system of government, which is implemented in Turkey and called as the party-presidential system, can be on political stability in comparison with the parliamentary system. In the first part of the study, the characteristics of the presidential system of government, and in the second part, the main reasons for political instability and the extent to which the presidential system of government can bring a solution to political instability were discussed.
Keywords: Government systems; presidential system of government; parliamentary system; political stability; separation of powers.